Dante e la figura dell’architetto - Tosco, Carlo (Opus Incertum, 2021)
The essay explores the relationship between Dante and the professional figure of the architect. In his works, both in Latin and in vernacular, the poet rarely deals with architecture and never describes prominent personalities of architects, either from the ancient world or the Middle Ages. Using philological tools, the essay investigates an interesting passage from De monarchia, where Dante affirms the superiority of the architect over all other categories of artists. The research shows how Dante’s opinion was shared by contemporary scholars, while the literary image of the architect was widespread in the scholastic culture of 13th century.